Antibiotic therapy costs at a Neonatal Intensive Care Unit at a philanthropic hospital - Neimah M. MAHMUD; Rodrigo J. FREDDO; Alex G. PEREIRA (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2022)
Objective: To evaluate the costs of antibacterials dispensed to patients admitted in a Neonatal Intensive Care Unit (UTIN) of a philanthropic hospital, over a one-year period. The total and unitary costs were analysed and the antibacterials were classified according to the ABC curve method. Methods: Study of direct analysis of therapy costs with injectable antibiotics for intravenous use, carried out from the assessment of dispensing data obtained from the institution managing software used for the hospital's central Pharmacy (SALUX System). The study comprised the period from January to December 2020. Results: A total of 191 patients were hospitalized throughout 2020 and 2.214 ampoules of various antibacterials were distributed, generating a total price of US$ 1.113.25. The drug cefepime, with a total cost of US$ 394.45 and 67 ampoules dispensed (35.4% of the total cost in antibacterials) reached the highest unit value. Ampicillin 500 mg and gentamicin 20 mg were the most dispensed drugs with 915 and 575 ampoules, respectively. According to the ABC curve classification, four antibacterials are grouped in category A and add up to 79.75% of the accumulated percentagem (AP) of total costs. Another four items are in category B (AP of 93.99%), while category C represented less than 10% of the total cost. Conclusion: The evidence from the study suggests that the prescription and dispensing of antibiotics for the NICU appear to be by the Pediatric Society guidelines since ampicillin and gentamicin were the most prescribed antibiotics with low cost for the economic administration of the hospital. Also, according to the global use of antibiotics, they do not show a high economic impact on the total costs of hospitalization and treatment of patients.